Spectral outputs of Yb3+/Pr3+ doped tellurite glasses for solid-state lighting - ERDEM, MURAT (My University, 2022)
© 2022, Turkish Chemical Society. All rights reserved.Downconversion processes which include visible and near-infrared luminescence at high energy excitation have been investigated in Yb3+/Pr3+ doped TeO2-ZnO-BaO glasses. The decrease of the DC emission intensities of Pr3+ ions with increasing mol% amount of Pr3+ ions is attributed to the concentration quenching. The CIE chromaticity coordinates of the perceived emission of Pr3+ ions shifted from orange to the red region depending on the increase in the pumping power. Consequently, Yb3+/Pr3+ doped TeO2-ZnO-BaO glasses could be used as functional optical materials for solid-state lighting applications.
Keywords: Kimya; Temel Bilimler; Chemistry; Natural Sciences; Temel Bilimler (SCI); Natural Sciences (SCI); CHEMISTRY; Genel Kimya; Fizik Bilimleri; General Chemistry; Physical Sciences; color parameters; Downconversion; lighting; tellurite glasses; Downconversion; tellurite glasses; color parameters; lighting